A free-floating mucin layer to investigate the effect of the local microenvironment in lungs on mucin-nanoparticle interactions. (1st March 2020) - Wan, Feng; Herzberg, Mikkel; Huang, Zheng; Hassenkam, Tue; Nielsen, Hanne M.
Abstract: Respiratory tract mucus represents an important barrier for pulmonary drug delivery. Understanding of mucin-nanoparticle interactions is a prerequisite for rational design of inhalable nanoparticles. In the present study, in order to establish a reliable quartz crystal microbalance with dissipation (QCM-D) approach to reveal the effect of the lung microenvironment on the mucin-nanoparticle interactions, we investigated the intrinsic features of the mucin layers immobilized onto sensors via chemical conjugation or physical adsorption by using atomic force microscopy (AFM) and QCM-D. Our results demonstrated that the covalently-grafted mucin layer responded more sensitively than the physically-adsorbed mucin layer to the local microenvironment shifting from PBS (pH 7.35 and ionic strength 30 mM) to PBS (pH 6.25 and ionic strength 150 mM) and resulted in a softer mucin layer with more hydrophobic areas exposed. Furthermore, using the QCM-D approach with the covalently-grafted mucin layer, we demonstrated the significant influence of the local microenvironment on the interaction of mucin with poly (lactic-co-glycolic acid)-based nanoparticles with different surface hydrophilicity. The present work underlines the QCM-D approach with a covalently-grafted mucin layer as a potent tool to elucidate the potential influence of local microenvironment on mucin-nanoparticle interactions. Statement of significance: Studying interactions between nanoengineered materials and biological systems plays a vital role in development of biomedical applications of nanoengineered materials. In this work, by employing a more biologically relevant, 'free-floating' mucin layer model, we demonstrate the significant impact of the lung microenvironment on the nature and the extent of the interaction between the mucin and the nanoparticles with different surface hydrophilicity. To the best of our knowledge, this is the first work describing the nanoscale properties of immobilized mucin layers and investigating the mucin-nanoparticle interactions with emphasis on the impact of local microenvironment in lungs. Thus, it is expected to have important consequences in rational design of inhalable nanoparticle delivery systems. Graphical abstract: Image, graphical abstract